Correlation of cognitive dysfunctions and diffusion tensor MRI measures in subjects with RRMS - Mirabile, Alessio; Susinna, Carla; Cipriano, Giovanni Luca; D’Aleo, Giangaetano; Rifici, Carmela; Sessa, Edoardo; Quartarone, Angelo; Lo Buono, Viviana (Frontiers in Aging Neuroscience, 2025)
BackgroundCognitive dysfunction is a common impairment observed in individuals with Multiple Sclerosis (MS), affecting key domains such as attention, information processing speed, memory, and executive functions. This deficit is typically identified through comprehensive neuropsychological assessments, which represent the gold standard for cognitive evaluation. In recent years, increasing efforts have been made to integrate neuropsychological findings with advanced neuroimaging techniques to better understand the neural substrates of cognitive dysfunction. Among these, Diffusion Tensor Imaging (DTI) has emerged as a valuable tool for investigating microstructural changes in white matter (WM) that may underlie cognitive deficits in MS. However, despite its clinical utility, the pathophysiological mechanisms contributing to cognitive impairment, particularly in subjects with Relapsing–Remitting MS (RRMS), remain complex and not yet fully understood. This review focuses on studies investigating WM alterations measured by DTI and their correlation with cognitive dysfunction as assessed through neuropsychological testing.MethodPapers were identified by searching in PubMed, Embase, Web of Science and Scopus databases from 2002 - the years, of first related published article, − to December 2024. From the initial 853, we included only 34 studies that met to eligibility criteria.ResultsIn subjects with RRMS, WM alterations, assessed through DTI, were found to correlate with cognitive dysfunction, as measured by standardized neuropsychological tests. These alterations were observed both in global WM and in specific regions, including the corpus callosum, thalamus, hippocampus, cerebellar structure, cingulum, and cerebral fascicles.ConclusionThese findings underscore the relevance of integrating neuropsychological assessment with advanced neuroimaging techniques, such as DTI, to enhance our understanding of cognitive impairment in RRMS. DTI-derived measures of WM integrity show promise as potential biomarkers of cognitive dysfunction, while cognitive profiling can help localize underlying neuropsychological damage. This integrated approach may improve early detection of cognitive alterations and support the development of targeted therapeutic strategies aimed at preserving cognitive functioning in individuals with MS.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD420251073195, Identifier CRD420251073195.